Extended reality technology for emergency medical service training: systematic review - Zhan Zhang; Maryam Moeini Meybodi; Aishwarya Ingale; Liza Karimova; Margarita Vinnikov (Frontiers in Disaster and Emergency Medicine)
BackgroundExtended reality (XR) technologies, which generally encompass virtual, augmented, and mixed reality, and realized through head-mounted devices, have been increasingly adopted to support Emergency Medical Services (EMS) training.ObjectiveThe objective of this review is to synthesize the current applications of immersive technologies in EMS training.MethodsA systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) framework. The studies were analyzed based on their objectives, methods, major findings, implemented technologies, and reported benefits and barriers.ResultsThe majority of reviewed studies used virtual reality (VR) technologies for EMS training. Key system features identified as effective included interactive user interfaces, task performance recording, monitoring and feedback, scenario editor and control, realism and presence, and multi-user collaboration. The studies primarily assessed four aspects of the implemented immersive technologies: technical feasibility, training effectiveness (e.g., clinical performance, knowledge acquisition), cost-effectiveness (e.g., cost savings, business models), and user experience (e.g., immersion, presence, cognitive load, usability, acceptance). Notable benefits highlighted included enhanced engagement, accessibility, cost-efficiency, standardization, and teamwork. Despite these advantages, challenges persist, which are categorized as ergonomic and human factor issues, usability problems, and technical limitations.ConclusionImmersive technologies have demonstrated significant potential to enhance EMS training by improving skill acquisition and readiness for high-stakes scenarios, such as massive casualty incidents or disasters. However, research in this area remains limited, requiring further investigation to address persistent challenges and optimize implementation.